2014
DOI: 10.1016/j.neulet.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Trio study and meta-analysis support the association of genetic variation at the serotonin transporter with early-onset obsessive–compulsive disorder

Abstract: Despite compelling evidence for major genetic contributions to the etiology of obsessive-compulsive disorder (OCD), few genetic variants have been consistently associated with this debilitating illness. Molecular genetic studies in children and adolescents with OCD are of particular interest, since early onset of the disease has been observed to be associated with increased familiality. We replicate here for the first time in early-onset OCD patients, a previously reported association of OCD with the common ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…In contrast, a recent meta-analysis that subdivided the 5-HTTLPR L allele into the high-functioning L A allele and the low-functioning L G allele (Hu et al, 2006), producing a triallelic form in which the L G allele is pooled with the S allele, reported that being an L A allele carrier was significantly associated with OCD (odds ratio = 1.251, 95% confidence interval = 1.048-1.492, p = 0.001) (Taylor, 2013). Just recently, we could replicate this finding of L A allele association with ealy onset OCD s well as within a meta-Analysis includng early and late onset OCD (Walitza et al, 2014b). However, up to now analysis of these gene variants using genetic imaging techniques in related conditions underscored the effects of the 5-HTTLPR S allele and brain activation.…”
Section: The Serotonergic Systemsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast, a recent meta-analysis that subdivided the 5-HTTLPR L allele into the high-functioning L A allele and the low-functioning L G allele (Hu et al, 2006), producing a triallelic form in which the L G allele is pooled with the S allele, reported that being an L A allele carrier was significantly associated with OCD (odds ratio = 1.251, 95% confidence interval = 1.048-1.492, p = 0.001) (Taylor, 2013). Just recently, we could replicate this finding of L A allele association with ealy onset OCD s well as within a meta-Analysis includng early and late onset OCD (Walitza et al, 2014b). However, up to now analysis of these gene variants using genetic imaging techniques in related conditions underscored the effects of the 5-HTTLPR S allele and brain activation.…”
Section: The Serotonergic Systemsupporting
confidence: 59%
“…This stipulation led to the retrieval of a small collection of manuscripts describing association analyses of genetic variants with neuroimaging techniques in OCD (n = 8). The present study focused on the most significant and nominally significant genes associated with OCD as inclusion criteria by cross-referencing these publications with GWAS and meta-analyzed genetic association (Azzam and Mathews, 2003;Lin, 2007;Pooley et al, 2007;Stewart et al, 2013aStewart et al, , 2013bTaylor, 2013;Walitza et al, 2014b). A publication by Hoexter et al (2009) was not included in the review because it did not include genetic association results in addition to their findings of single-photon emission computed tomography or magnetic resonance imaging in OCD.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from studies on convenience samples suggests that early onset OCD is associated with a number of distinguishing features, of relevance for clinical intervention, including comorbidity with neurodevelopmental disorders such as tic disorder and attention deficit hyperactivity disorder (ADHD) and familial clustering suggesting a greater genetic contribution (Walitza et al, 2008, Walitza et al, 2010, Taylor 2011. Indeed, in some studies, early-onset OCD has been associated with specific gene variants of serotonergic, dopaminergic and glutamatergic receptors and synaptic brain related genes, neurotrophic and transcription factors (Walitza et al, 2014, Grünblatt et al, 2017. Symmetry, ordering and sexual or religious symptoms are also associated with early-onset OCD (Labad et al, 2008), possibly linked to comorbidity with tic disorders and tic-specific symptoms.…”
Section: Epidemiology Of Ocdmentioning
confidence: 99%
“…Furthermore, symptom exacerbation generally occurs when targeting receptors that negatively regulate presynaptic serotonin release [20,21], suggesting that deficient serotonin signalling contributes to OCD. In addition, associations of serotonin transporter gene polymorphisms with OCD [22][23][24][25][26][27][28] have led to speculation that OCD is associated with a hyposerotonergic state. However, many inconsistencies have made it difficult to isolate specific abnormalities within the serotonergic system.…”
Section: (B) Evidence From Clinical Obsessive-compulsive Disorder Stumentioning
confidence: 99%
“…These preclinical data may seem somewhat at odds with some clinical data. For instance, the utility of SRIs in treating OCD symptoms [19,64], decreased serotonin transporter availability [28,31,[65][66][67][68][69], and associations of polymorphisms of the genes encoding serotonin transporter [22][23][24][25][26][27][28] and serotonin 2A receptor [23] proteins with OCD have led to speculation that OCD is associated with a hypo-serotonergic state. However, it is important to note that the serotonin hypothesis has mixed support [1].…”
Section: (A) Serotonergic Disruptions In Sapap-3 Knockout Micementioning
confidence: 99%